SIMULATION MODELING OF LOGGING HARVESTER MOVEMENTS DURING SELECTIVE LOGGING - Rukomojnikov, Konstantin; Sergeeva, Tatiana (Journal of Applied Engineering Science, 2024)
The purpose of this research is to substantiate the mathematical regularities of the harvester operation, allowing for rapid technical calculations of labor costs with a sufficient level of reliability when performing various logging operations. The article describes the simulation model of harvester movement in the cutting area, created by the authors to analyze the operation of the harvester at various logging sites. Examples of visualization of the program and the results obtained with its use are given. Four-factor experimental plan was drawn up with varying factors at four levels. The results obtained during the simulation have been statistically processed. The analyzed elements of the cycle time are: the average time of pointing the manipulator at a tree, the average time of moving a fallen tree to the processing zone and the average time of moving the harvester between working positions per felled tree. The regression dependencies obtained as a result of the analysis are based on four indicators. Such indicators are: the total stock of wood per hectare, the share of the felled component of the stand, the amount of undergrowth (rowan, bird cherry, willow, etc.) in the cutting area, the average volume of the tree in the cutting area. The found patterns give the researcher a general idea of the effectiveness of the equipment in specific natural conditions of cutting areas. The use of the acquired knowledge in the analysis of harvester performance will improve the accuracy of planning the work of logging crews.
Keywords: regression dependence, cut-to-length harvesting, labor costs, cutting area